GAYA ARSITEKTUR ISTANA KEKHALIFAHAN MASA ABBASIYAH - Aminy, Aisyah (UIN Sumatera Utara, 2021)
Architecture is the work of architects designed to build spaces in a building with the desired function and purpose. Buildings in royal palaces are also the design and composition of the work of architects formed in accordance with the developments that occurred during the kingdom and contain certain meanings in each arrangement of the corners of the room. The architecture of a building has certain characteristics in each era, including the architectural style of the Abbasid caliphate palace buildings. This research aims to explain the architectural style of the Abbasid caliphate palace. This research uses data collection techniques with library research methods. The result of this research is to know the types and styles of architecture of the Abbasid period, the architectural style of the caliphate palace and the influence of other architectural styles in the construction of the caliphate palace building.Keyword : Architecture, Palace, Abbasid